UTILIZATION OF RED GUAVA SEEDS INTO RENGGINANG PUJI SERI - Aritonang, Evawany; Sarumpaet, Sora Muda (Talenta Publisher, 2019)
Rengginang is thick crackers made from pulut (sticky rice) which are dried in the sun and then fried in hot oil. Economically, Rengginang business is a very profitable business because it is a snack that can be consumed daily by the community. One way to increase the nutritional content of Rengginang pulut is by adding red guava. Laboratory results show that red guava contains Fe, Vitamin C and Zn. Annysa UKM fostered by the Syariah Cooperative Community of Al-Ikhlas produces guava fruit syrup, starfruit syrup, red guava dodol and starfruit dodol. So far, the red guava pulp has not been utilized by Annysa UKM. Then the service team gave a new innovation in food diversification by utilizing red guava pulp into a mixture making Rengginang. The method of approach is carried out with socialization, discussion, training, demonstration and assistance. The dedication team tested 3 recipes of guava red with a composition of 5 gr, 7.5 gr and 10 gr. After the recipe was tested, it was applied to Annysa UKM on August 1, 2019. As a result, Annysa UKM members were skilled in processing glutinous rice and red guava. The dedication team also facilitated the facilities and infrastructure in the form of spiner and cylinders needed for the development of the manufacturing of Rengginang pujiseri in the Annysa UKM group.